Young Businesspeople’s Entrepreneurial Perceptions and Intentions to Contribute to Local Communities: A Case Study of the Cultured Pearl Industry in Mie, Japan - Max Weeks; Hiroko Oe; Yasuyuki Yamaoka; Takuya Hirata (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2021)
A number of theoretical frameworks attempt to help those in disadvantaged areas by encouraging growth in local industries created in those areas. However, as far as the authors are aware, not all of these attempts have been successful. The case discussed here is that of the cultured pearl industry, a traditional Japanese industry. In particular, the research focuses on the cultured pearl industry in Mie Prefecture, located in the western part of Mainland Japan, and the attitudes of young entrepreneurs who aim to support its sustainable development. A quantitative approach was applied to survey data collected from 170 respondents living in and originating from Mie Prefecture, through which this research attempts to identify the factors motivating young entrepreneurs to contribute to the industrial revitalisation of their local communities. Four potential motivating factors for young entrepreneurs to contribute to their local communities were initially hypothesised (sense of community involvement, attachment to community, economic value, and non-economic value, such as that related to community ties). These were then analysed and examined based on a factor analysis and regression model. The analytical results indicated that three of the four factors were significant in estimating the willingness of young entrepreneurs to contribute to the community, with the exception being the third factor, ‘economic value’. This finding may not be immediately generalisable due to the small amount of data available for the study and the need to compare individual respondent demographics and response trends. For example, it may be that the participants in this survey were already successful entrepreneurs with no financial concerns and a desire to contribute to the local pearl businesses and community development in addition to their primary businesses. Thus, a future research goal is to evaluate the results of this study through a detailed survey that considers the respondents' individual attributes. However, as a pilot test, this study indicates that the young generation, with its entrepreneurial spirit, does not necessarily have economic value as their primary goal. Instead, they may be more attentive to sociocultural factors; in particular, they may be prepared to take a stand for the sustainable development of their local communities.